Refugees’ Trajectories in Switzerland: Impact of Residence Permits on Labour Market Integration - Bertrand, Anne-Laure (My University, 2019)
Life course trajectories of refugee populations in European countries highly depend on the various statuses and residence permits that are assigned to them. Taking the case study of Switzerland, this article aims at showing the impact of the legal framework on refugees’ chances of labour market integration. The term “refugee” here refers to all the individuals who came to Switzerland seeking asylum, no matter the outcome of the asylum procedure – and not only to those who obtained the status as defined by the 1951 Geneva Convention. In this study, the longitudinal follow-up of the individuals is made possible by the matching of data from several population registers. From a descriptive point of view, sequence analysis allows the visualization of refugees’ trajectories from their arrival in the country – in terms of both residence permits and of labour market participation. Survival analysis models then show the concordance between the administrative status and the economic status, the access to more stable permits increasing significantly the chances of labour market integration. As a consequence, those who remain for many years with the most precarious permits (asylum seekers and provisionally admitted persons) go through a process of cumulative disadvantage. Although the economic vulnerability of refugees has been highlighted previously, this paper shows that within the refugee population, the host countries’ legislation creates an additional hierarchy, based on the residence permits, that further widens inequalities.
Keywords: Refugees; residence permits; legislation; administrative status; labour market integration; longitudinal analysis; population registers; Switzerland